Cloning, characterization and impact of up- and down-regulating subabul cinnamyl alcohol dehydrogenase (CAD) gene on plant growth and lignin profiles in transgenic tobacco - Sirisha, V. L.; Prashant, S.; Kumar, D. Ranadheer; Pramod, S.; Jalaja, N.; Kumari, P. Hima; Rao, P. Maheshwari; Rao, S. Nageswara; Mishra, Preeti; Karumanchi, S. Rao; Khan, Bashir Mohammad; Kishor, P. B. Kavi (Plant Growth Regulation, 2012)
Both cDNA including 5'UTR and 3'UTR and genomic clones of cinnamyl alcohol dehydrogenase (CAD) were isolated and characterized from a pulp-yielding leguminous tree Leucaena leucocephala (LlCAD1). The deduced amino acid sequence shared high identity with orthologous sequences of Acacia mangium x Acacia auriculiformis (83%), Medicago sativa (83%), Nicotiana tabaccum (83%) and Aralia cordata (81%). Full length cDNA contained 78 bases of 5'UTR and 283 bases of 3'UTR, while the genomic clone contained 5 exons and 4 introns. Western blot analysis revealed elevated expression of LlCAD1 in seedling roots and shoots compared to leaves. Sense and antisense CAD tobacco transgenics showed increased and reduced CAD activity accompanied by a change in monomeric lignin composition. Histochemical staining of lignin in down-regulated plants suggested an increase in aldehyde units and a decrease in S/G ratio. Down-regulation of CAD resulted in accumulation of syringic, ferulic, p-coumaric and sinapic acids compared to untransformed controls. These observations were validated by anatomical studies of down-regulated transgenic stems which showed thin walled, elongated phloem and xylem fibres, accompanied by a reduction in the density of vessel elements and amount of secondary xylem when compared to untransformed plants. Furthermore, Klason lignin analysis of CAD antisense transgenics showed 7-32% reduced lignin and normal phenotype as compared to untransformed plants. Such a reduction was not noticed in up-regulated transgenics. These results demonstrate a unique opportunity to explore the significant role that down-regulation of CAD gene plays in reducing lignin content thereby offering potential benefits to the pulp and paper industry.
Keywords: Cinnamyl alcohol dehydrogenase; Lignin down-regulation; Subabul (Leucaena leucocephala); Tobacco